Physical and mechanical properties of RAFT-stabilised collagen gels for tissue engineering applications. (November 2019) - Kayal, Celine; Shipley, Rebecca J.; Phillips, James B.
Abstract: Cell behavior is influenced by the mechanical and structural properties of their substrate environment. Also, materials mechanically resistant to surgical handling and similar to the host site are required in tissue engineering to minimise the chance of an adverse host response. RAFT-stabilisation is a commercially available technique for creating stabilised hydrogels. Properties of RAFT-stabilised collagen (RsC) gels are governed by size, composition and arrangement of fibrils and their interaction with the fluid trapped within the matrix. The stabilisation process, using hydrophilic porous absorbers, produces dense matrices by rapid expulsion of fluid, and the structure obtained has mechanical properties suitable for tissue engineering. However, protocols to define and compare the physical properties and mechanical behavior of RAFT-stabilised collagen gels are not standardised across the field. Here, we investigate the fundamental mechanical and structural properties of RsC gels, and propose a new empirical relationship that correlates the measured stiffness of gels to varying frequency of strain oscillation. The results provide quantitative data characterising this extracellular environment for future tissue engineering studies.